Continuous and Intermittent Planetary Ball Milling Effects on the Alloying of a Bismuth Antimony Telluride Powder Mixture - Georgios Samourgkanidis; Theodora Kyratsi (Inorganics, 2023)
This study investigates the effects of continuous and in-steps mechanical alloying of a bismuth antimony telluride powder mixture (Bi<semantics>0.4</semantics>Sb<semantics>1.6</semantics>Te<semantics>3.0</semantics>) via the mechanical planetary ball milling (PBM) process as a function of milling time and powder mixture amount. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the phase, composition, and morphology of the alloy. The alloyed powder with the optimum PBM conditions was then hot pressed (HP), and its thermoelectric properties were further investigated. The results on the alloying of the powder mixture showed that due to the high agglomeration tendency of BST during the PBM process, a significant deviation occurs in the development of a single-phase state over time when the powder mixture is milled continuously and in-steps. ’In-steps’ refers to the procedure of interrupting the PBM process and detaching the agglomerated powder adhering to the inner walls of the vessel. This task was repeated every hour and a half of the PBM process for a total of 12 h, and the results were compared with those of the 12 h continuous PBM process of the same mixture. In addition, the procedure was repeated with different amounts of mixture (100 g and 150 g) to determine the most efficient method of producing the material as a function of time. As for the thermoelectric profile of the powder, the data showed results in direct agreement with those in the literature.